MiR-223 is dispensable for platelet production and function in mice - Leierseder, Simon; Petzold, Tobias; Zhang, Lin; Loyer, Xavier; Massberg, Steffen; Engelhardt, Stefan (Thrombosis and Haemostasis, 2013)
MicroRNAs (miRNAs) are key physiological regulators in multiple cell types. Here, we assessed platelet production and function in mice deficient in miR-223, one of the most abundantly expressed miRNAs in platelets and megakaryocytes. We found platelet number, size, lifespan as well as surface expression of platelet adhesion receptors to be unchanged in miR-223-deficient mice. Likewise, loss of miR-223 did not affect platelet activation, adhesion and aggregation and also had no effect on bleeding times. Moreover, miR-223 null megakaryocytes developed normally and were capable to form pro-platelets. However, we detected a transient delay in the recovery of platelet numbers following antibody-induced platelet depletion in miR-223-deficient animals. This delay was not observed after transplantation of bone marrow from miR-223-deficient animals into wild-type recipients, indicating a non-cell-autonomous role of miR-223 for thrombopoiesis. Overall, our data indicate a surprisingly modest role of miR-223 in platelet production, while the function of platelets does not seem to depend on miR-223.
Keywords: MicroRNA; platelets; megakaryocytes; transgenic mice